Transient Analysis of the Self Excited Induction Generator Subjected to Grid Disturbances - Malika Imadouchene (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
The present paper analyzes the consequences of short grid voltages interruptions on grid-connected self-induction generator, particularly, on the currents and electromagnetic torque of the generator. These effects depend on several variables such as the phase difference between the grid voltages and those of the generator, the magnitude of the grid voltage and the generator currents at the instant of reconnection to the grid. The approach has been used for studying the effects of these grid disturbances on the self-excited induction generator; is a numerical approach. In the numerical approach, which is based on the dynamic d-q model of the induction generator, the effect of magnetic saturation is accurately accounted for. This numerical model has been validated by experimental measurements taken from an induction generator test bench. The analysis focuses on the amplitudes of the peaks of the currents and torque during short interruptions especially at the reconnection of the grid voltage. The results obtained from the numerical model are compared to the measured ones.